Social inequality and higher education. The case of Uruguay - Santiaviago, Carina; Passarini , José; Or´ós, Carla; Yozzi, Mariana; De León, Fabiana (Tierra Infinita, 2022)
The results of an initial review of specialized literature on access to higher education and inequality in Uruguay are presented; in particular, at the University of the Republic (hereinafter Udelar), the main higher education institution in the country. The study refers to social gaps in income, permanence and completion of the tertiary level of training. The literary review allows us to establish that the characteristics of the Udelar, with unrestricted admission and free admission, are insufficient to reduce social differences in access, permanence and graduation from the institution